1999
DOI: 10.1007/s000110050513
|View full text |Cite
|
Sign up to set email alerts
|

Eosinophils and neutrophils in biopsies from the middle ear of atopic children with otitis media with effusion

Abstract: The results of this study show the feasibility of using specific antibodies to identify eosinophils and neutrophils in the middle ear. The initial data suggest that atopic children with OME have higher numbers of such cells as compared to non-OME controls.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…EPO encodes erythropoietin, a protein that controls erythropoiesis and production of red blood cells [33]. In addition, the middle ear in subjects having OM with effusion demonstrated elevated levels of EPO, eosinophils and neutrophils [34]. Allergic inflammation with elevated eosinophils in the middle ear can cause OM with effusion [35].…”
Section: Discussionmentioning
confidence: 99%
“…EPO encodes erythropoietin, a protein that controls erythropoiesis and production of red blood cells [33]. In addition, the middle ear in subjects having OM with effusion demonstrated elevated levels of EPO, eosinophils and neutrophils [34]. Allergic inflammation with elevated eosinophils in the middle ear can cause OM with effusion [35].…”
Section: Discussionmentioning
confidence: 99%
“…Histopathologic and biochemical studies confirmed the presence of these cell types in the effusion and in the subepithelial space of the middle ear cleft (13). Amin et al (14) described neutrophils and eosinophils in biopsies from middle ear mucosa using an immunohistochemistry method. Hurst and Verge (6,15) verified the presence of eosinophils, mast cells, and neutrophils by measuring the levels of the cell-specific enzymes in the effusion.…”
Section: Discussionmentioning
confidence: 99%
“…22 Messenger RNA for IL-8 is actively produced in the cells found in MEE associated with viral infections but is not found to arise from mucosal cells. 23 Biopsy studies demonstrate a greater number of eosinophils and neutrophils in the mucus than in the mucosa of ears of atopic patients with chronic OME and a significant and similar ratio of neutrophils and eosinophils both in the mucus and mucosa, 24 indicating a proportional influx by both cells into the middle ear of atopic patients.…”
Section: Commentmentioning
confidence: 94%